2014
DOI: 10.1038/npp.2014.131
|View full text |Cite
|
Sign up to set email alerts
|

A Cocaine Context Renews Drug Seeking Preferentially in a Subset of Individuals

Abstract: Addiction is characterized by a high propensity for relapse, in part because cues associated with drugs can acquire Pavlovian incentive motivational properties, and acting as incentive stimuli, such cues can instigate and invigorate drug-seeking behavior. There is, however, considerable individual variation in the propensity to attribute incentive salience to reward cues. Discrete and localizable reward cues act as much more effective incentive stimuli in some rats ('sign-trackers', STs), than others ('goal-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 43 publications
8
57
1
Order By: Relevance
“…6d). These data further highlight the notion that GTs and STs capture different forms of reward learning, both of which may be relevant to addiction liability (Saunders and Robinson 2010, Saunders et al 2013, Saunders et al 2014, Kawa et al 2016, Pitchers et al 2017), and both of which appear to be mediated by the PVT (Haight and Flagel 2014, Haight et al 2015, Haight et al 2017). …”
Section: Resultssupporting
confidence: 62%
“…6d). These data further highlight the notion that GTs and STs capture different forms of reward learning, both of which may be relevant to addiction liability (Saunders and Robinson 2010, Saunders et al 2013, Saunders et al 2014, Kawa et al 2016, Pitchers et al 2017), and both of which appear to be mediated by the PVT (Haight and Flagel 2014, Haight et al 2015, Haight et al 2017). …”
Section: Resultssupporting
confidence: 62%
“…For example, ablating neurogenesis in the hippocampus during forced abstinence following cocaine self-administration increases the propensity for context-dependent reinstatement (Noonan et al 2010), while reducing the number of adult-born hippocampal neurons increases time spent in a cocaine-paired context in a test of conditioned place preference (Castilla-Ortega et al 2016b). These data are congruent with the fact that goal-trackers appear to be more susceptible to reinstatement in response to drug-associated contexts (Saunders et al 2014) and that bLR rats are more sensitive to changes in hippocampal neurogenesis. Taken together, the relationship between adolescent cocaine exposure, the regulation of hippocampal cell genesis, and the enhanced expression of goal-tracking behavior suggested by the current findings, warrants further investigation.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, while sign-trackers are more responsive to discrete drug-associated cues (Flagel et al 2011; Yager et al 2014) and more likely to exhibit cue- and drug-induced reinstatement of drug-seeking behavior relative to goal-trackers (Saunders and Robinson 2010, 2011) after relatively brief periods of cocaine self-administration, both phenotypes exhibit addiction-related behaviors following prolonged intermittent access to cocaine (Kawa et al 2016). In addition, goal-trackers have been shown to exhibit enhanced reinstatement of drug-seeking behavior in response to drug-associated contexts (Saunders et al 2014). Similar to outbred goal- and sign-trackers, we have postulated that bLRs and bHRs may represent two distinct paths to “addiction”.…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenics also have a disproportionately high incidence of substance abuse (Dixon 1999;Dixon et al 1991;Gearon et al 2001), which could also be linked to alterations in the neural circuits that control the assignment of motivational value to reward (drug)-paired stimuli. We trained MAM and sham animals in a Pavlovian conditioned approach task that affords the opportunity to characterize the acquisition of a cue-reward association, as well as the attribution of incentive salience, the latter being predictive of multiple behaviors reminiscent of drug addiction (Saunders et al 2014;Saunders and Robinson 2010;Saunders et al 2013). In the present study, we found no strong evidence for a difference between MAM and sham animals in terms of the target or magnitude of their cue-triggered approach behavior, when such behavior was triggered.…”
Section: Motivation and Cue-reward Learning In Mam Animalscontrasting
confidence: 55%